English Language Teachers’ Knowledge toward the Implementation of Independent Learning - Ayu Surayya; Ari Prasetyaningtum; Astrid Dwimaulani (UIBU, 2025)
Independent Learning emphasizes student autonomy, critical thinking, and creativity, positioning teachers as facilitators in the learning process. English teachers, tasked with implementing this approach, must align their content knowledge and pedagogical understanding with its learner-centered principles. The study adopts a small scale quantitative survey which distributed to 35 sample of English teachers across elementary, junior, and senior high schools in Indonesia that invited by a Telegram and Whatsapp Group invitation and sampled insidentaly. The findings indicate that while most English teachers hold strong beliefs in the importance of Independent Learning, their knowledge of its principles remains shallow, creating a disconnect between endorsement and practical implementation. Thus, this findings aim to provide insights into teachers’ cognitive and affective dimensions influencing policy implementation, offering theoretical advancements in education and practical implications for professional development, policy formulation, and classroom practices. By examining the intersection of teachers' knowledge and beliefs, this research seeks to support effective integration of Independent Learning in English language education, fostering an environment conducive to holistic student development.